2019
DOI: 10.3390/ijms20236081
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Catechol Based-Polyelectrolyte Complex Coatings for Controlled Release of Bortezomib

Abstract: To overcome the high relapse rate of multiple myeloma (MM), a drug delivery coating for functionalization of bone substitution materials (BSM) is reported based on adhesive, catechol-containing and stimuli-responsive polyelectrolyte complexes (PECs). This system is designed to deliver the MM drug bortezomib (BZM) directly to the anatomical site of action. To establish a gradual BZM release, the naturally occurring caffeic acid (CA) is coupled oxidatively to form poly(caffeic acid) (PCA), which is used as a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Compounds 8, 10, and 12, instead, showed moderate effects at higher concentrations and weak effects at 25 mM. On the contrary, apigenin (14) and luteolin (15) exhibited strong effects on NCI and OPM-2 cells at concentrations of 50 and 100 mM and were still moderately active at 25 mM. Moreover, both compounds showed moderate effects on U266 cells over the whole concentration range.…”
Section: Cytotoxicity Measurementsmentioning
confidence: 94%
See 3 more Smart Citations
“…Compounds 8, 10, and 12, instead, showed moderate effects at higher concentrations and weak effects at 25 mM. On the contrary, apigenin (14) and luteolin (15) exhibited strong effects on NCI and OPM-2 cells at concentrations of 50 and 100 mM and were still moderately active at 25 mM. Moreover, both compounds showed moderate effects on U266 cells over the whole concentration range.…”
Section: Cytotoxicity Measurementsmentioning
confidence: 94%
“…The same accounts for cichoric acid (13), which showed higher effects against all three myeloma cell lines than against healthy PBMC and HS5 cells. The most cytotoxic substances in this screen were apigenin (14) and luteolin (15). All tested cells displayed enhanced apoptosis with a clear preference of cell death in blood-borne cells.…”
Section: Determination Of Selectivitymentioning
confidence: 95%
See 2 more Smart Citations
“…Similar to the first investigation, the authors found an initial burst release of adsorbed bortezomib followed by a gradual elution over 2 days. With a thermal stimulus of 42 • C, bortezomib release was accelerated due to conformational changes of the thermo-responsive coating [229]. Regarding thermally triggered drug release for bone regeneration, in vivo investigations are still lacking.…”
Section: Temperaturementioning
confidence: 99%